Les écosystèmes des montagnes du Haut Tell friguien occidental : dynamique de la population et friches - Hamza Ayari (Revue de Géographie Alpine)
The fallows, which prevail predominately in the mountainous landscapes of the Tunisian High Tell in 2018, have been source of conflicts between local population and the forestall administration in the colonial and the national period since the end of the 19th century. They represent a left ecological footprint on the landscapes of the Mediterranean hinterland due to the different forms of pressure on the woody ecosystems related to the population dynamics. Since the 19th century, the succession of the political and economic contexts led the populations to follow movements of installation and waves of deforestation at high altitudes during their dislocation by the agrarian colonization, then in plains with the equipment by elementary services. The fieldwork was guided by two questions:Did the abandonment, which led to land clearing, promote forest regeneration?Do the absentees’ ways of exploitation accelerate deforestation and erosion?It seems that the evolution of the fallows has followed different paths in function based on the chronological abandonment and bioclimatic aptitudes of the ecosystems.